2020
DOI: 10.4158/accr-2020-0474
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypocalcemia Following Parathyroidectomy for Giant Parathyroid Adenoma

Abstract: Objective: Giant parathyroid adenomas (GPAs) are a rare type of parathyroid adenoma (PA) weighing >2 to 3 g. The objective of this manuscript is to report a case of giant parathyroid adenoma and highlight the risk of postoperative hypocalcemia. Methods: We describe the presentation and work-up of a woman with GPA confirmed with histopathology as well as management of postoperative hypocalcemia. Results: A 66-year-old Caucasian female with chronic fatigue was found to have elevated calcium levels at 13.7 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Unfortunately, recent studies showed that even this method is not very accurate and many patients cannot be diagnosed only upon the results of both of these examinations [10]. APA are extremely rare and have only been described 23 times in literature [12,27]. They lack specific criteria from histopathological point of view, it is not possible to differentiate them from benign adenomas and cancerous lesions neither by imaging methods nor macroscopically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, recent studies showed that even this method is not very accurate and many patients cannot be diagnosed only upon the results of both of these examinations [10]. APA are extremely rare and have only been described 23 times in literature [12,27]. They lack specific criteria from histopathological point of view, it is not possible to differentiate them from benign adenomas and cancerous lesions neither by imaging methods nor macroscopically.…”
Section: Discussionmentioning
confidence: 99%
“…They lack specific criteria from histopathological point of view, it is not possible to differentiate them from benign adenomas and cancerous lesions neither by imaging methods nor macroscopically. Microscopically, they have some features of carcinomathey adhere to contiguous structures, bends of fibrosis, solid trabecular growth, mitotic activity, but they do not invade the capsule, what is a hallmark of malignancy [12,13,26]. Although, the lack of specific criteria for histopathologic makes it extremely hard to always correctly diagnose the Atypical Adenoma (APA).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, recent studies showed that even this method is not very accurate and many patients cannot be diagnosed only upon the results of both of these examinations [10]. APA are extremely rare and have only been described 23 times in literature [12,27]. They lack speci c criteria from histopathological point of view, it is not possible to differentiate them from benign adenomas and cancerous lesions neither by imaging methods nor macroscopically.…”
Section: Discussionmentioning
confidence: 99%
“…They lack speci c criteria from histopathological point of view, it is not possible to differentiate them from benign adenomas and cancerous lesions neither by imaging methods nor macroscopically. Microscopically, they have some features of carcinoma -they adhere to contiguous structures, bends of brosis, solid trabecular growth, mitotic activity, but they do not invade the capsule, what is a hallmark of malignancy [12,13,26].…”
Section: Discussionmentioning
confidence: 99%
“… 60 Clearance of Levels II–V is associated with a lower risk of recurrence. 61 The role of therapeutic lymph node dissection for treatment of thyroid cancer nodal metastases is well-accepted for the clinically positive or cN1 disease, but the value of routine prophylactic Level VI (central) neck dissection and lateral neck dissection for cN0 disease remains unclear. 10 , 11 , 42 , 53 - 55 There are limited data to prove that prophylactic dissection of microscopic PTC LNM improves disease-specific outcomes.…”
Section: The 2021 Interim Clinical Practice Guidelinesmentioning
confidence: 99%